2021
DOI: 10.5195/jmla.2021.1216
|View full text |Cite
|
Sign up to set email alerts
|

Racial, gender, sexual, and disability identities of the Journal of the Medical Library Association’s editorial board, reviewers, and authors

Abstract: The Journal of the Medical Library Association (JMLA) recently issued a call for submissions that recognize and address social injustices; speak to diversity, equity, and inclusion in our workforce and among our user populations; and share critical perspectives on health sciences librarianship as well as those on any topic within JMLA’s scope written by authors who are Black, Indigenous, or People of Color. We also committed to creating more equitable opportunities for authors, reviewers, and editorial board m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…To inform our efforts to create more inclusive and equitable opportunities for authors, reviewers, and editorial board members, we conducted a demographic survey of all individuals who served as JMLA editorial board members or reviewers or had submitted a manuscript to JMLA between 2018 and 2020. We found that most respondents were white, heterosexual, women, and people without disabilities or impairments, similar to the demographic characteristics of the MLA membership [ 7 ]. While not altogether surprising, this finding suggests that JMLA lacked representation and contributions from individuals who do not meet the demographic “norm” of health sciences librarians and information specialists.…”
Section: Why Did We Reexamine the Editorial Board Selection Process?mentioning
confidence: 84%
“…To inform our efforts to create more inclusive and equitable opportunities for authors, reviewers, and editorial board members, we conducted a demographic survey of all individuals who served as JMLA editorial board members or reviewers or had submitted a manuscript to JMLA between 2018 and 2020. We found that most respondents were white, heterosexual, women, and people without disabilities or impairments, similar to the demographic characteristics of the MLA membership [ 7 ]. While not altogether surprising, this finding suggests that JMLA lacked representation and contributions from individuals who do not meet the demographic “norm” of health sciences librarians and information specialists.…”
Section: Why Did We Reexamine the Editorial Board Selection Process?mentioning
confidence: 84%
“…In the context of SCI, researchers are increasingly engaging research-end users, for example, clinicians, policy-makers and PWLE [ 35 ], to bridge the gap between research and practice. Representation of people with disabilities in journal practices and policies, however, remains limited [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Journal editorial boards, editors, and reviewers have been described as gatekeepers of knowledge [ 1 ], influencing the landscape of published research. By broadening the scope of publishable material, editors and reviewers with diverse backgrounds, perspectives, and life experiences construct an equitable peer review [ 1 3 ] and mitigate the influence of social bias, inaccessible infrastructure, and discrimination in the process [ 4 , 5 ]. Biases arising from the exclusion of the perspectives and opinions of an affected community can lead to an undervaluing of the research, and the ultimate goal of improving patient outcomes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe it behooves the members of the profession of medical librarianship to find funding and carry out surveys and studies to elucidate the information needed to encourage changes in our profession that will inspire the welcoming of more diversity into our profession and our information centers, wherever they may be. The recent paper by Akers et al in this journal is to be commended for their efforts in this direction [ 20 ].…”
mentioning
confidence: 99%